Influenza virus neuraminidase regulates host CD8+ T-cell response in mice - Chung-Yi Wu (Nature Portfolio, 2020)
Chung-Yi Wu et al. demonstrate a role of neuraminidase (NA) for Influenza A viruse (IAV)-specific CD8+ T-cell response and virion assembly. When mice are vaccinated with the live attenuated NA-defective IAV, they are protected from the upcoming IAV infection. This study provides insights into the development strategies of universal influenza vaccines.